2018
DOI: 10.4300/jgme-d-18-00059.1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Simulation-Based Assessments of Emergency Medicine Residents

Abstract: Background Gender-related disparities persist in medicine and medical education. Prior work has found differences in medical education assessments based on gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Twenty studies were conducted in the United States, 14–33 13 were performed in Canada, 34–46 three took place in Australia, 47–49 and two were conducted in Taiwan 50,51 . Thirty‐three studies involved resident physicians, 15,17–23,25–32,34–47,49,50 four studies involved medical students, 14,16,24,33 and one did not report the learner level 48 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty studies were conducted in the United States, 14–33 13 were performed in Canada, 34–46 three took place in Australia, 47–49 and two were conducted in Taiwan 50,51 . Thirty‐three studies involved resident physicians, 15,17–23,25–32,34–47,49,50 four studies involved medical students, 14,16,24,33 and one did not report the learner level 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies were conducted in the United States, 14–33 13 were performed in Canada, 34–46 three took place in Australia, 47–49 and two were conducted in Taiwan 50,51 . Thirty‐three studies involved resident physicians, 15,17–23,25–32,34–47,49,50 four studies involved medical students, 14,16,24,33 and one did not report the learner level 48 . Twenty‐two were prospective studies, 14,16,17,22–28,30,31,33,37,38,40–42,46–48,51 nine were retrospective, 18–20,32,35,39,44,45,50 five were qualitative studies, 21,29,34,43,49 and two were descriptive studies 15,36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing standardized assessments in controlled or simulated environments may also be helpful, especially if there are discrepant evaluations for trainees. In a 2018 study of medical simulations for EM residents conducted with a scripted and standardized assessments found that there were no differences in scores due to resident or rater gender, supporting these assessments to limit bias 17 . These simulated assessments can be part of a larger portfolio of multisource evaluation tools utilized by CCCs to consider when assigning semiannual competency ratings.…”
Section: Discussionmentioning
confidence: 93%